Seeking to Understand the Impact of Collaboration on Intercultural Communication Apprehension - Jacobi, Laura (Journal of International Students, 2020)
To assess the impact of collaboration on intercultural communication apprehension (ICA), this mixed-methods study compared ICA levels of 41 domestic and international undergraduates who participated in collaborative activities with 79 students in a control group. International student participants came from a variety of countries, while the majority of domestic students were White. A Mann-Whitney U test was used to determine if there were differences in Personal Report of Intercultural Communication Apprehension scores across time between the experimental and control groups. The co-instructors of the collaborative group were also interviewed. Quantitative results indicate no significant differences in ICA levels due to the collaboration. Interview data reveal the potential for collaboration to reduce ICA and for in-group bias and lack of motivation to act as barriers in reducing ICA.